Problems with attempted chorioretinal venous anastomosis by laser for nonischemic CRVO and BRVO - ŞAHİN, ÖZLEM (KARGER, 2005)
Purpose: To report the complications and long-term results of laser-induced chorioretinal venous anastomosis in vein occlusions. Patients and Methods: Eight consecutive eyes, 3 with central retinal vein (CRVO) and 5 with branch retinal vein occlusion (BRVO), were observed for up to 5 years after attempted laser-induced chorioretinal venous anastomosis. Results: Successful chorioretinal venous anastomoses were created in 2 (25%) eyes. Patients had severe complications, including vitreous hemorrhage, choroidal neovascular membrane, choriovitreal neovascularization, rubeosis iridis and neovascular glaucoma. Conclusion: The utilization of a chorioretinal venous anastomosis by laser with proposed laser settings as a therapeutic modality should be further analyzed, and a careful long-term follow-up must be done to avoid vision-threatening complications. Copyright (C) 2005 S. Karger AG, Basel.
Keywords: argon laser; chorioretinal venous anastomosis; central retinal vein occlusion; branch retinal vein occlusion; MEMBRANE